Contribution of maternal copy number variations to false‐positive fetal trisomies detected by noninvasive prenatal testing. (24th February 2017) - Zhou, Xiya; Sui, Lili; Xu, Yalan; Song, Yijun; Qi, Qingwei; Zhang, Jianguang; Zhu, Hongmin; Sun, Huaiyu; Tian, Feng; Xu, Mengnan; Cram, David S.; Liu, Juntao
Abstract: Objective: The aim of the study was to determine the contribution and significance of maternal copy number variations (CNVs) to false‐positive noninvasive prenatal testing (NIPT) trisomy results. Methods: A total of 112 021 patients were referred for NIPT. Fetal aneuploidy testing was performed using low coverage massively parallel sequencing, and results reported as chromosome Z‐scores. Copy number variation sequencing (CNV‐Seq) was used to detect maternal DNA CNVs. Results: Confirmatory amniocentesis and karyotyping of 563 of 781 patients (72%) receiving a positive trisomy result revealed 489 true and 74 false positives. In 6 of these 74 patients (8.1%), CNV‐Seq revealed non‐pathogenic maternal duplications (1.76–10.90 megabases) on the chromosome associated with the fetal trisomy. There was a strong correlation of higher Z‐scores with increasing size of the maternal CNVs ( R 2  = 0.94). When the contribution of the maternal CNV‐Seq reads to chromosome Z‐scores were removed, all original Z‐scores shifted to the normal range. Conclusions: Maternal CNVs can potentially contribute to a small but significant number of false‐positive fetal trisomies detected by NIPT. To avoid unnecessary invasive procedures and better manage patients, we recommend that confirmatory maternal DNA sequencing is performed when the NIPT methodology used indicates a high risk of a maternal CNV. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Known genetic causes of false‐positive noninvasive prenatal testing (NIPT) results include vanishing twins, maternal tumors, and confined placental mosaicism. Depending on NIPT methodology, maternal copy number variations can also cause false‐positive results. What does this study add? Maternal chromosome duplications were found to be associated with up to 10% of false‐positive fetal trisomy NIPT results. High chromosome Z‐scores can indicate a false‐positive trisomy because of the presence of a maternal duplication. For all positive NIPT results where the risk of a maternal copy number variation is high, we recommend maternal DNA sequencing to avoid unnecessary confirmatory invasive procedures.